Hook [videorecording (Blu-Ray + DVD)] - Hoffman, Dustin, 1937-; Williams, Robin, 1951-2014; Roberts, Julia, 1967-; Hoskins, Bob; Smith, Maggie, 1934-2024; Korsmo, Charlie, 1978-; Barrie, J. M. (James Matthew), 1860-1937; Hart, James V.; Marmo, Malia Scotch; Spielberg, Steven, 1946- (Sony Pictures Home Entertainment, 2011)
A high-flying adventure from the magic of Steven Spielberg, Hook stars Robin Williams as a grown-up Peter Pan and Dustin Hoffman as the infamous Captain Hook.